Health Education England, Local Education and Training Boards (LETBs) and reform of healthcare education: implications for surgical training - Wild, Jonathan RL (BMC Surg, 2015)
BACKGROUND: National Health Service (NHS) reforms have changed the structure of postgraduate healthcare education and training. With a Government mandate that promotes multi-professional education and training aligned with policy driven initiatives, this article highlights concerns over the impact that these changes may have on surgical training. DISCUSSION: The creation of Health Education England (HEE) and its local education and training boards (LETBs), which are dominated by NHS healthcare providers, should result in greater accountability of employers in workforce planning, enhanced local responsibility and increased transparency of funding allocation. However, these changes may also create a potential poacher-turned-gamekeeper role of employers, who now have responsibility for junior doctors’ training. Analysis of LETB membership reveals a dearth of representation of surgeons, who comprise only 2% of board members, with the input of trainees also seemingly overlooked. A lack of engagement with the LETBs by the independent sector is a concern with increasing numbers of training opportunities potentially being lost as a result. The new system also needs to recognise the specific training needs required by the craft specialties given the demands of technical skill acquisition, in particular regarding the provision of simulation training facilities and trainer recognition. However, training budget cuts may result in a disproportionate reduction of funding for surgical training. Surgical training posts will also be endangered, opportunities for out-of-programme experience and research may also decline and further costs are likely to be passed onto the trainee. SUMMARY: Although there are several facets to the recent reforms of the healthcare education and training system that have potential to improve surgical training, concerns need to be addressed. Engagement from the independent sector and further clarification on how the LETBs will be aligned with commissioning services are also required. Surgical training is in danger of taking a back seat to Government mandated priorities. Representation of trainees and surgeons on LETB committees is essential to ensure a surgical viewpoint so that the training needs of the future consultant workforce meet the demands of a 21(st) century health service.